Rewriting the bacterial glycocalyx via Suzuki-Miyaura cross-coupling - Spicer, C; Davis, B (Royal Society of Chemistry, 2013)
Suzuki-Miyaura cross-coupling has been used to couple novel carbohydrate-based boronic acids, site-selectively, to the surface of E. coli at an unnatural amino acid. In this way, benign metal-catalyzed cellular switching allowed modulation of interactions with biomolecular partners via prokaryotic O-glycosylation mimics.